Association of the metabolic score for insulin resistance with cardiovascular diseases, cardiovascular and all-cause mortality in Chinese hypertensive population - Zhang, Liting; Yu, Chao; Wang, Tao; Zhou, Wei; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2024)
Little is known about the relationship between the metabolic score for insulin resistance (METS-IR) and the prognosis of hypertensive patients in China. Objective: To investigate the association between the novel non-insulin-based METS-IR index and the cardiovascular composite endpoints and all-cause mortality in Chinese hypertensive participants. Design, setting, and participants: This cohort study used data from the China H-Type Hypertension Project, a long-term prospective cohort consisting of 14234 hypertensive patients in southern China, with a baseline from March to August 2018. The median follow-up period (IQR) for hypertension was 3.94 (3.74-4.14) years, as of 2022. The data analysis period is from July 2023 to September 2023. Exposures: METS-IR index of participants in the Chinese H-type hypertension project. The calculation formula for METS-IR is (Ln (2 × FPG) +TG) × BMI/Ln (HDL-C). Main outcomes and measures: Cardiovascular events and cardiovascular, all-cause mortality were identified by linking the cohort database with the health care system through October, 2023. Results: A total of 14220 participants were included in this study. The prevalence rates of cardiovascular disease (CVD), cardiovascular death, and all-cause death were 2.59% (369/14220), 2.79% (397/14220), and 5.66% (805/14220), respectively. After adjusting for confounding factors in the multivariate logistic regression analysis models, the METS-IR index was significantly positively correlated with CVD, and cardiovascular, all-cause mortality, whether as a categorical or continuous variable. Layered analysis showed that the METS-IR index of hypertensive participants in different subgroups was positively correlated with the endpoint event.Conclusions and relevance: this large, prospective cohort study demonstrated that the METS-IR index, a new IR evaluation index, were independently associated with a higher risk of the cardiovascular composite endpoint and all-cause mortality among Chinese hypertensive population. Importantly, our finding provides an independent indicator for evaluating the prognosis of hypertensive patients.